Literary hero and time as the main problem in Mir Jalal’s stories - Rasulova, A.A. (Karagandy University of the name of academician E.A. Buketov, 2025)
This article explores the central role of the literary hero and the concept of time as fundamental issues in the short stories of Mir Jalal, a prominent Azerbaijani writer and literary critic. By analyzing selected narratives, the study examines how Mir Jalal constructs his protagonists as reflections of social and psychological realities in the context of the historical transformations of the 20th century. Special attention is given to the temporal structure of his stories, revealing how time functions not only as a chronological framework but also as a narrative device that shapes character development and deepens thematic meaning. The article highlights the interplay between individual consciousness and collective memory, demonstrating how Mir Jalal’s heroes navigate personal identity amidst socio-political changes. Ultimately, the study underscores the writer’s engagement with the notion of time and his nuanced portrayal of the intellectual and moral dilemmas faced by his characters. Scientific Novelty. The scientific novelty of this study lies in its comprehensive analysis of the interrelationship between the literary hero and the category of time in Mir Jalal's stories—an aspect that has received limited scholarly attention to date. Unlike traditional interpretations that primarily focus on ideological or stylistic features, this article highlights the philosophical and structural role of time as a central narrative device. The research reveals how Mir Jalal uses time not only to frame historical and social contexts but also to construct the internal world of his protagonists, thereby offering a deeper understanding of the psychological and moral dimensions of his literary heroes. This approach offers a fresh perspective on Mir Jalal’s narrative techniques and contributes to the broader discourse on Azerbaijani literary modernism. Methodology. This research is grounded in textual and comparative analysis of selected short stories by Mir Jalal, with particular attention to the representation of the literary hero and the temporal structure of the narratives. Combining literary theory, narratological approaches, and historical-contextual analysis, the study investigates how the author’s treatment of time influences both the psychological depth and the ideological positioning of his characters. The research employs qualitative and interpretive methods to explore the symbolic and structural functions of time in shaping character development and constructing thematic meaning. Through close reading and critical interpretation, the study aims to reveal the innovative ways in which Mir Jalal engages with the concepts of individuality, memory, and historical consciousness.
Әдеби батыр және уақыт Мир Жалал әңгімелеріндегі басты мәселе ретінде
Литературный герой и время как главная проблема в рассказах Мира Джалала
Keywords: Mir Jalal; a literary hero; a storyteller; a writer with a time problem; an original style